Urbanization and its effects on income diversification of farming households in Adama district, Ethiopia - Wakitole Dadi; Messay Mulegeta; Negussie Simie (Cogent Economics & Finance, 2022)
Urbanization remains a public policy challenge in developing countries, particularly in Sub-Saharan Africa, where fast growth rates have been observed. This study aims to investigate the effect of urbanization on the income diversification of farm households in the Adama district of the Oromia regional state. We used data collected from two groups of farm households based on their distance from the urban center. Families residing close to urban areas are categorized as treated and controlled for the remaining counterpart. The study employed both descriptive and inferential data analysis. Multinomial logistic regression analysis revealed that farming households in urban areas diversify their income to farm and unskilled non-farm activities more than rural households far away from urban centers. The research shows that increasing urbanization by one unit causes a decrease in farming activities by 32%, and farming and non-farm activities increase by 24%. The result also indicated that households with higher age and their consumption expenditure determinant factors for more likely to diversify their income to unskilled non-farm activities. The result proved that urbanization limits farming households' capacity to generate income from agriculture and pushes them to diversify to non-farming income-generating activities. Governments should therefore design robust strategies and facilitate the provision of agricultural technologies. The regional state and small financial enterprises should also assist displaced households in expanding their income-generating activities.
Keywords: 330; Income diversification; marginal effect; multinomial logistic regression; Oromia Region; urbanization